Distribution and Utilization Management Zis (Zakat, Infaq and Alms) Based on Asnaf at Baznas Bulukumba Regency - Wilda, Syahdatul (Yayasan Amerta Insan Unggul, 2022)
This research is a type of qualitative research with the aim of knowing the Management of Distribution and Utilization of ZIS (zakat, infaq and alms) based on Asnaf at BAZNAS Bulukumba Regency. The data obtained was the result of interviews from WK II in the distribution sector and four BAZNAS Bulukumba Regency staff which were shared and related to the problem studied. In this research, the data sources used in data collection include primary data and secondary data. The data collection methods used in this research are observation, interviews and documentation. There are two issues studied in writing this thesis, namely: (1) how to manage the distribution and utilization of ZIS based on ASNAF at BAZNAS Bulukumba Regency, (2) what factors hinder the distribution and utilization of ZIS based on ASNAF at BAZNAS Bulukumba Regency. From the results of this research it can be concluded that: 1) management of the distribution and utilization of ZIS based on ASNAF has been implemented quite well. This is proven by the running of management functions, namely planning, organizing, implementing and supervising, although at the organizing stage it has not yet been implemented optimally. This happens because limited human resources, especially in the areas of distribution and utilization. The distribution and utilization of ZIS cannot yet be distributed to all asnaf because there is no asnaf riqab in Bulukumba Regency. (2) factors inhibiting the distribution and utilization of ZIS based on asnaf, apart from the wide reach in Bulukumba Regency, also at the assessment stage the community is not open to the assets they own, limited human resources are also an obstacle to the distribution and utilization of ZIS which of course the staff will be overwhelmed in distributing ZIS.